Uji Aktivitas Antifungi Kombinasi Ekstrak Etanol Kulit Pisang Kepok (Musa paradisiaca L.) dan Kulit Jeruk Manis (Citrus sinensis) terhadap Candida albicans Penyebab Keputihan Patologis Secara In Vitro - Yulia, Inelvi; Prima, Heppy Setya (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Pathological vaginal discharge (Candidiasis) is a reproductive health problem experienced by more than 50% of women throughout the world. Candida albicans is the main cause of pathological vaginal discharge. This disease is characterized by yellow to greenish discharge, odor, and itching to the point of bleeding which can cause death. Antifungal drugs used to treat pathological vaginal discharge can have several side effects. Therefore, the urgency of this research is to find natural alternatives for pathological vaginal discharge drugs, such as sweet orange peel and kepok banana peel which contain bioactive compounds that can inhibit the growth of Candida albicans. The aim of this study was to test the antifungal activity of a combination of ethanol extracts of sweet orange peel and kepok banana peel against Candida albicans in vitro. This research uses laboratory experimental methods. The results showed that all combinations of ethanol extracts of sweet orange peel and kepok banana peel could inhibit the growth of Candida albicans. The inhibitory power of each extract combination is categorized as moderate to very strong. According to the one-way ANOVA statistical test, all combinations were significantly different (p < 0.05). The ethanol extract of sweet orange peel contains flavonoids, alkaloids, phenolics and steroids, while the kepok banana peel extract contains phytochemical compounds such as flavonoids, phenolics, triterpenoids and alkaloids.